The Role of Digital Innovation as A MSME Business Resilience Strategy During the Covid Pandemic - Yusuf Iskandar (Budapest International Research and Critics University, 2022)
As long as the COVID-19 pandemic continues, MSMEs will experience setbacks and face various problems. They will continue to do so if there is no adaptation from the perpetrators to increase their productivity again. The low productivity of MSMEs causes the profit also generated to decrease. This is a threat to the national economy. Therefore, efforts and strategies are needed to save MSMEs so they can continue to survive amid the COVID-19 pandemic, even after the pandemic. The strategy that can be used, for example, is the MSME digitalization development strategy from the Kemenkop MSMEs, namely: preparing MSME business actors to increase human resources and intervene in improving MSME business processes which will later be implemented in several programs. For the strategy to be successful, MSMEs need to innovate business through genuine efforts, such as using digital marketing and creative content, as well as improving quality and service so that more potential customers are captured, and it is hoped that repeat purchases will occur in the future. Buying and selling transactions mean that the opportunity for MSMEs to survive is more significant, and the Indonesian economy can move positively. This article was written using the literature study method by collecting empirical data sources related to the topics discussed in the article. The result is that the digitization program has several strategies for MSMEs to maintain their business, including (1) Utilizing the digital platform as much as possible, (2) Mastering digital marketing skills, (3) improving product quality.